Archaeology Argot: kernos (The Biblical archaeology review, 2020)
A kernos (plural kernoi) is a distinctive type of ancient Greek pottery introduced to the Iron Age Holy Land by Aegean traders and immigrants, likely from Cyprus. It is composed of a hollow ring with several smaller vessels—sometimes in the shape of anthropomorphic figures—attached to it. These smaller vessels held liquids used for libation […]